Infrastructural Adequacy in Implementing Competence-Based Education (CBE) in Grade Four Agriculture: A Case of Public Primary Schools in Njoro Sub-County, Kenya - Alex Karani (Journal of Social Transformation and Regional Development, 2025)
This study examines the adequacy of institutional infrastructural resources for teaching competence-based Grade Four agriculture in public primary schools within Njoro Sub-County, Kenya. The key challenges identified include the lack of essential facilities such as laboratories, agriculture stores, workshops for tool repairs, and agriculture rooms/libraries. The study aimed to assess the availability of these resources and their impact on agricultural education. A descriptive survey design was employed, utilizing a questionnaire to collect data from 96 agriculture teachers across 96 schools. The findings highlight significant infrastructure gaps, particularly in school farms and water supply, which are critical for effective agricultural education. The study concludes that improving infrastructure, alongside regular teacher training and policy implementation, is crucial to enhance the quality of agricultural education and the socio-economic prospects of students.